2009
DOI: 10.1093/humrep/dep432
|View full text |Cite
|
Sign up to set email alerts
|

Signal mechanisms of vascular endothelial growth factor and interleukin-8 in ovarian hyperstimulation syndrome: dopamine targets their common pathways

Abstract: Our results suggest that VEGF and IL-8 secreted from corpora luteae may play major roles in OHSS. Delineation of signal pathways would be helpful for treatment. Dopamine may block VEGF- and IL-8-induced endothelial permeability by inhibiting common VEGFR-2 dependent signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 44 publications
5
30
0
2
Order By: Relevance
“…These results suggest that the ANGPT1 content in FF from these patients is partially responsible for the morphological change within endothelial cells. These results are consistent with data obtained previously by other authors and by our laboratory (Chen et al 2010;Scotti et al 2013). Chen et al (2010) showed that FF from OHSS women remarkably induces actin redistribution, in comparison with the morphology of control endothelial cells in culture medium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggest that the ANGPT1 content in FF from these patients is partially responsible for the morphological change within endothelial cells. These results are consistent with data obtained previously by other authors and by our laboratory (Chen et al 2010;Scotti et al 2013). Chen et al (2010) showed that FF from OHSS women remarkably induces actin redistribution, in comparison with the morphology of control endothelial cells in culture medium.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with data obtained previously by other authors and by our laboratory (Chen et al 2010;Scotti et al 2013). Chen et al (2010) showed that FF from OHSS women remarkably induces actin redistribution, in comparison with the morphology of control endothelial cells in culture medium. Besides, we have previously observed that the incubation of FF from women at risk of OHSS with an ANGPT1-neutralising antibody decreases endothelial cell migration (Scotti et al 2013), considering that actin reorganisation is a prerequisite for cell migration and angiogenesis (Lauffenburger and Horwitz 1996;Menager et al 1999).…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been reported that IL-8 stimulates the autocrine activation of VEGFR-2 in endothelial cells by the activation of NF-κB through the caspase recruitment domain and membrane-associated guanylate kinase-like domain-containing protein/B-cell lymphoma-10/mucosa-associated lymphoid tissue lymphoma translocation-1 complex (47). IL-8 activates chemokine (C-X-C motif) receptor 1/2 on endothelial cells, leading to VEGFR-2 transactivation, and this is required for IL-8-induced endothelial permeability (56,57). However, there is little evidence concerning the association between IL-8 and VEGFR-2 in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, early endometriotic lesions are characterized by dense vascularization. Several angiogenic factors (such as vascular endothelial growth factor [VEGF], interleukin-8 and placental growth factor) have been shown to contribute to the establishment and progression of endometriosis, 9 and it has been suggested that antiangiogenesis therapy is a potential treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11 Endostatin has also been reported to interfere with fibroblast growth factor-2-induced signal transduction. 9 On the basis of these findings, endostatin appears to have the potential to become one of the most valuable antiangiogenic agents in the treatment of cancer. 12 The effect of transferring the endostatin gene into endometriotic lesions has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%